Pachymic Acid Inhibits Growth and Induces Apoptosis of Pancreatic Cancer In Vitro and In Vivo by Targeting ER Stress - Cheng, Shujie (PLoS One, 2015)
Pachymic acid (PA) is a purified triterpene extracted from medicinal fungus Poria cocos. In this paper, we investigated the anticancer effect of PA on human chemotherapy resistant pancreatic cancer. PA triggered apoptosis in gemcitabine-resistant pancreatic cancer cells PANC-1 and MIA PaCa-2. Comparative gene expression array analysis demonstrated that endoplasmic reticulum (ER) stress was induced by PA through activation of heat shock response and unfolded protein response related genes. Induced ER stress was confirmed by increasing expression of XBP-1s, ATF4, Hsp70, CHOP and phospho-eIF2α. Moreover, ER stress inhibitor tauroursodeoxycholic acid (TUDCA) blocked PA induced apoptosis. In addition, 25 mg kg(-1) of PA significantly suppressed MIA PaCa-2 tumor growth in vivo without toxicity, which correlated with induction of apoptosis and expression of ER stress related proteins in tumor tissues. Taken together, growth inhibition and induction of apoptosis by PA in gemcitabine-resistant pancreatic cancer cells were associated with ER stress activation both in vitro and in vivo. PA may be potentially exploited for the use in treatment of chemotherapy resistant pancreatic cancer.